Safety of Chitosan Bandages in Shellfish Allergic Patients - Waibel, Kirk H.; Haney, Brian; Moore, Merrideth; Whisman, Bonnie; Gomez, Robert (Military medicine, 2011)
In 2005, the Office of the Surgeon General mandated that every soldier carry a HemCon bandage. Made from chitosan, a polysaccharide derived from shrimp shells, this bandage effectively stops bleeding. There are no studies reporting the safety of this bandage in shellfish allergic patients. Patients who reported shellfish allergy were recruited. Initial assessment included a detailed history, IgE skin prick testing (SPT), and serum testing to shellfish allergens. Participants who demonstrated specific shellfish IgE underwent a bandage challenge. Nineteen participants were enrolled; 10 completed the study. Seven (70%) were male and the average age was 44.8 + 10 years. Nine (90%) reported a shrimp allergy history and five (50%) reported multiple shellfish allergies. All participants completing the study had positive SPT and serum IgE testing to at least one shellfish; eight (80%) had shrimp positive SPT and ten (100%) demonstrated shrimp-specific IgE. No participant had a positive SPT to chitosan powder or experienced an adverse reaction during bandage challenges. No protein bands were visualized during gel electrophoresis analysis of chitosan powder. All participants tolerated the HemCon bandage without reaction. This is the first study demonstrating the safety of this bandage in shellfish allergic subjects.